IMPLEMENTATION OF DELIBERATION PRINCIPLES IN HOUSEHOLD LIFE: A TAFSIR BASED STUDY - Zulayka Muchtar; Sohrah; Rosmini; Anita Marwing; Feri Eko Wahyudi (UIN Palopo, 2025)
Consultation (shura) is a fundamental principle in Islamic teachings that functions not only as political ethics, but also as a collective method for social and family decision-making. Although many studies highlight consultation in the context of state affairs, studies on its implementation in household dynamics are still limited. This study aims to analyze the concept and meaning of musyawarah in Surah Ali Imran (3): 159, Surah al-Syura (42): 38, and Surah al-Baqarah (2): 233 based on the interpretations of classical and contemporary exegetes, as well as analyzing the relevance and implementation of these principles in building harmony in household life. This study uses a thematic interpretation (maudhu'i) method. Data collection was conducted through library research by referring to classical and contemporary interpretation literature. The results of the study show that deliberation in the Qur'an includes the principles of gentleness, equality, mutual agreement, collective participation, and moral responsibility. Surah Ali Imran (3): 159 emphasizes the importance of gentle and communicative leadership; Surah al-Syura (42): 38 places deliberation as a key characteristic of a community of believers, including within the family environment; while Surah al-Baqarah (2):233 emphasizes deliberation as a fundamental principle in family relationships, especially between husband and wife. These principles have proven relevant in building a harmonious, dialogical, and just household life Keywords: Shura, Thematic Tafsir, Family Life, Surah Ali Imran, al-Shura and al-Baqarah